(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Reading comprehension is a significant element of reading. Research shows that digital technology can assist language learners in improving their reading comprehension. This scoping review aimed to examine and describe research papers concentrating on using Technology-Enhanced Learning (TEL) for teaching reading comprehension to lower-level English as a Foreign Language (EFL) learners in a non-English-speaking context. Databases like ERIC, OneSearch, Google Scholar, Scopus, and ResearchGate were used to categorize peer-reviewed research articles between 2014 and 2025. Thirty papers that met the inclusion criteria were selected for analysis. Research papers concentrated on English-speaking contexts, and theoretical studies were excluded, choosing only non-English teaching settings and those containing evaluative evidence of TEL interventions. Results show that multimedia applications and AI-driven tools are broadly used in teaching reading comprehension in the EFL context. TEL is indicated as an accelerator in student engagement, personalized learning, and reading comprehension skills. However, TEL has some challenges, such as teacher professional development, accessibility problems, and the sustainability of technology-based interventions. Future investigations should examine efficient TEL strategies to incorporate into the EFL curriculum and assess their cross-cultural adaptability.